Characterization of the Heme Pocket Structure and Ligand Binding Kinetics of Non-symbiotic Hemoglobins from the Model Legume Lotus japonicus - Calvo-Begueria, Laura; Cuypers, Bert; Van Doorslaer, Sabine; Abbruzzetti, Stefania; Bruno, Stefano; Berghmans, Herald; Dewilde, Sylvia; Ramos, Javier; Viappiani, Cristiano; Becana, Manuel (Frontiers in Plant Science, 2017)
Plant hemoglobins (Hbs) are found in nodules of legumes and actinorhizal plants but also in nonsymbiotic organs of monocots and dicots. Nonsymbiotic Hbs have been classified into two phylogenetic groups. Class 1 Hbs show an extremely high O2 affinity and are induced by hypoxia and nitric oxide (NO), whereas class 2 Hbs have moderate O2 affinity and are induced by cold and cytokinins. The functions of nonsymbiotic Hbs are still unclear, but some of them rely on the capacity of hemes to bind diatomic ligands and catalyze the NO dioxygenase reaction (oxyferrous Hb + NO → ferric Hb + nitrate). Moreover, NO may nitrosylate Cys residues of proteins. It is therefore important to determine the ligand binding properties of the hemes and the role of Cys residues. Here, we have addressed these issues with the two class 1 Hbs (LjGlb1-1 and LjGlb1-2) and the single class 2 Hb (LjGlb2) of Lotus japonicus, which is a model legume to facilitate the transfer of genetic and biochemical information into crops. We have used carbon monoxide (CO) as a model ligand and resonance Raman, laser flash photolysis, and stopped-flow spectroscopies to unveil major differences in the heme environments and ligand binding kinetics of the three proteins, which suggest non-redundant functions. In the deoxyferrous state, LjGlb1-1 is partially hexacoordinate, whereas LjGlb1-2 shows complete hexacoordination (behaving like class 2 Hbs) and LjGlb2 is mostly pentacoordinate (unlike other class 2 Hbs). LjGlb1-1 binds CO very strongly by stabilizing it through hydrogen bonding, but LjGlb1-2 and LjGlb2 show lower CO stabilization. The changes in CO stabilization would explain the different affinities of the three proteins for gaseous ligands. These affinities are determined by the dissociation rates and follow the order LjGlb1-1 > LjGlb1-2 > LjGlb2. Mutations LjGlb1-1 C78S and LjGlb1-2 C79S caused important alterations in protein dynamics and stability, indicating a structural role of those Cys residues, whereas mutation LjGlb1-1 C8S had a smaller effect. The three proteins and their mutant derivatives exhibited similarly high rates of NO consumption, which were due to NO dioxygenase activity of the hemes and not to nitrosylation of Cys residues.